2018
DOI: 10.1021/acsomega.7b01815
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Thermodynamic Parameters of DNA Double Helix Unwinding with the Help of Mechanical Methods

Abstract: For the first time, rupture event scanning (REVS) procedure based on quartz crystal microbalance (QCM) and involving only mechanical action was used to determine the height of the energy barrier for dsDNA unwinding. Melting point was determined with the help of this procedure. To determine the thermodynamic parameters including enthalpy, DNA denaturation was represented as a unimolecular process. This allowed us to recover the energy profiles from the experimental data obtained by force measurements at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our analyses of the mechanical properties of an 18 bp DNA sensor stretched from three locations confirm that DNA-based sensors are more suitable for detecting single force level corresponding to dissociation of the two strands rather than detecting a range of forces. Although the rupture force values we observe in our DNA sensor simulations are higher than experimentally observed, as expected because of the higher loading rate (47,(49)(50)(51)(52)(53)(54), the trends are consistent with experimental results (58), which report rupture forces that are low for unzipping (stretching forces P1) and are high for shearing (stretching from P2). Furthermore, the DNA sensor pulled from P3 is predicted to exhibit a mechanical response that is a combination of what we observed when stretching from P1 and P2 in simulations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our analyses of the mechanical properties of an 18 bp DNA sensor stretched from three locations confirm that DNA-based sensors are more suitable for detecting single force level corresponding to dissociation of the two strands rather than detecting a range of forces. Although the rupture force values we observe in our DNA sensor simulations are higher than experimentally observed, as expected because of the higher loading rate (47,(49)(50)(51)(52)(53)(54), the trends are consistent with experimental results (58), which report rupture forces that are low for unzipping (stretching forces P1) and are high for shearing (stretching from P2). Furthermore, the DNA sensor pulled from P3 is predicted to exhibit a mechanical response that is a combination of what we observed when stretching from P1 and P2 in simulations.…”
Section: Discussionsupporting
confidence: 92%
“…The simulations methods and results presented in here could also aid the design of new sensors with strategically placed FRET pairs, different sequences, or sequence lengths. Other applications and outlooks of this work include guiding the implementation of sensors in hybrid molecular devices requiring force sensitivity (58,60) or guiding tether design in force spectroscopy techniques like optical trapping or AFM, as demonstrated by Ott et al (61).…”
Section: Discussionmentioning
confidence: 96%
“…Analyzing the separation of the strands' centers of mass showed that a maximum distance of 45 Å is sufficient for complete dissociation of the duplexes of oligonucleotides with a length of 4 to 9 bp, and for complexes of 14 and 16 bp in size, the distance should be increased to 60 Å. With the reaction coordinate chosen in this manner, the dissociation of the two strands for most oligonucleotide duplexes proceeded in accordance with the unzipping model (Cantor, Schimmel, 1980;Volkov, Solov'yov, 2009), which involves the unwinding of the double helix from one of the ends, or in accordance with a mixed shearing/unzipping mode (Mosayebi et al, 2015;Kurus, Dultsev, 2018). An example of alterations of oligonucleotide conformations along the reaction coordinate is given in Supplementary Material 1 1 .…”
Section: Resultsmentioning
confidence: 99%